Perencanaan Perawatan Mesin Kompresor Pada PT. Es Muda Perkasa Dengan Metode Reliability Centered Maintenance (RCM) - Ikramullah Zein; Dewi Mulyati; Ilham Saputra (Jurnal Serambi Engineering, 2019)
Compressor at PT. Es Muda Perkasa that commonly failure is at unit D. So that need to optimize the compressor at unit D with finding the failure of the parts of the compressor and making the schedule of maintenance program to minimize the failure of the ice machine. This study using Reliability Centered Maintenance (RCM) method, which applicate Grey FMEA to determine the priority of the machine maintenance. After conducting and implementing the RCM method, it was found that the failure occurs at Low-Pressure and High-Pressure Pump at compressor unit D, and sub-part failure happen on bearing, due to small coefficient, which is 0.566 where it become primarily failure component. For the next maintenance, using schedule on condition task on bearing parts of the machine could minimize the failure of the parts on the machine